2012
DOI: 10.5966/sctm.2011-0039
|View full text |Cite
|
Sign up to set email alerts
|

Human Adult Dental Pulp Stem Cells Enhance Poststroke Functional Recovery Through Non-Neural Replacement Mechanisms

Abstract: Human adult dental pulp stem cells (DPSCs), derived from third molar teeth, are multipotent and have the capacity to differentiate into neurons under inductive conditions both in vitro and following transplantation into the avian embryo. In this study, we demonstrate that the intracerebral transplantation of human DPSCs 24 hours following focal cerebral ischemia in a rodent model resulted in significant improvement in forelimb sensorimotor function at 4 weeks post-treatment. At this time, 2.3 ± 0.7% of engraft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
161
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(166 citation statements)
references
References 59 publications
5
161
0
Order By: Relevance
“…Many categories of cerebral apoplexy models have shown that nerve protection was primarily terminated through an indirect mechanism. Recent studies have reported that stem cell-derived extracellular vesicles exert an effect on alleviating movement coordination disorders after focal cerebral ischemia [10,11]. In the current study, we compared and found that extracellular vesicles and MSCs possess an identical effect.…”
Section: Discussionmentioning
confidence: 76%
“…Many categories of cerebral apoplexy models have shown that nerve protection was primarily terminated through an indirect mechanism. Recent studies have reported that stem cell-derived extracellular vesicles exert an effect on alleviating movement coordination disorders after focal cerebral ischemia [10,11]. In the current study, we compared and found that extracellular vesicles and MSCs possess an identical effect.…”
Section: Discussionmentioning
confidence: 76%
“…NGF and its receptor tropomyosin-related kinase A (TrkA) play a crucial role in the development and function of the nervous system. DPSCs exert an intriguing regenerative potential in the damaged central nervous system of the rodent, that is attributed in part to their multiple-differentiation ability to replace lost neurons, but mainly to the production of neurotrophic factors including NGF and brain derived neurotrophic factor (BDNF) that promote neuron survival and axon guidance [92,93]. NGF is involved in the guidance of trigeminal axons in embryonic teeth.…”
Section: Effects Of Growth Factors On Dpsc Proliferation and Differenmentioning
confidence: 99%
“…However, this is a highly invasive procedure and is associated with an increased mortality rate of approximately 10% when administered acutely in rodent stroke models. 2 As such, acute IC transplantation may not be a clinically viable model.…”
Section: Introductionmentioning
confidence: 99%
“…2 This field of study was sparked by the ability of stem cells to populate areas and replace the function of many divergent tissue types. Transplantation of stem cells provides the potential to extend the post-stroke recovery of function beyond what is possible by endogenous recovery alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation